Mapping the Evolution of E-Government in ASEAN: A Bibliometric Analysis (2011–2024) - Sudirman, Faturachman Alputra; Alam, Syamsul (Pusjar SKPP Lembaga Administrasi Negara, 2026)
The rapid digital transformation of governance has become a critical policy agenda across the globe, with ASEAN countries emerging as important laboratories for E-Government adoption. The regional diversity highlights the need to understand how digital governance evolves within Southeast Asia. This study analyses research trends and patterns related to E-Government in the ASEAN region from 2011 to 2024 using a bibliometric approach. Despite being central to digital government transformation in enhancing administrative functions and public engagement, the adoption of E-Government in ASEAN still faces persistent challenges, including the digital divide, limited ICT infrastructure, and political-economic disparities. Through bibliometric analysis of Scopus-indexed publications, this study examines the growth of research outputs, identifies leading contributors among researchers and institutions, and explores evolving thematic trends in the field. Findings reveal that Thailand, Malaysia, and Indonesia dominate the scholarly landscape. Furthermore, recent studies have increasingly shifted from focusing on technical implementation to addressing broader issues such as socio-economic impacts, international trade, and governance reforms. The results underscore the importance of policy measures that promote digital inclusion and enhance technological literacy. Strengthening transparency and building public trust emerge as crucial components of successful E-Government initiatives. For future research, the study recommends more focused case studies across ASEAN countries and further investigation into the effects of digital policies on key sectors like education and healthcare. This study is limited to English-language publications in Scopus; subsequent research could incorporate a wider range of data sources to provide a more inclusive regional perspective.